Kontestasi Syari’at Islam dan Westernisasi dalam Kehidupan Masyarakat Aceh - Mohd. Reza Pahlevi (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
Westernization is a cause for the phenomenon of violations of Islamic law in Aceh. These various forms of foreign culture have entered into people's lives. Foreign culture that entered so quickly accepted and adopted in his life. Even though Aceh is one of the areas with the largest Muslim majority population in Indonesia and has the rules contained in the Qanun regarding the implementation of Islamic law. The purpose of this study is to answer how the implementation of Islamic law in Aceh and the extent of the impact that occurs due to westernization in the midst of the implementation of Islamic law in Aceh. The research method that the author uses is using qualitative research methods. The results of the research are that westernization in Aceh is dominant to the negative side and is contrary to the teachings of Islam and Islamic law (Qanun). In people's lives, violations such as how to dress that is not in accordance with the Shari'a, promiscuity, being alone with the opposite sex who is not a mahram, content on social media but not dressing according to religious advice and so on have become commonplace and are no longer taboo in society.